Family dynamics in face of Alzheimer's in one of its members - Barbara Alana Vizzachi; Celina Daspett; Maria Goreti da Silva Cruz; Ana Lúcia de Moraes Horta (SciELO, 2015)
Abstract OBJECTIVE To understand the family dynamics when there is a member in the residence with Alzheimer's disease. METHOD A study of qualitative approach, using the creative sensitive method (CSM), and with participation of two families who had a member with Alzheimer's disease at home. RESULTS Three categories emerged: Effects of Alzheimer's disease and the family dynamics; Development process of Alzheimer's disease and Coping strategies in face of the disease. CONCLUSION It was possible to know the manifestations and consequences of Alzheimer's disease in the family, such as mutual help, the mobilization of resources to activate memories of the past, spirituality and faith. There was also understanding of the structure of family dynamics.